OS09.6.A Factors predicting mood disorders, health related quality of life and sexual disturbances in adults with glioma: a retrospective study. (5th September 2022) - Leonetti, A; Puglisi, G; Rossi, M; Conti Nibali, M; Sciortino, T; Gay, L; Vigano', L; Fornia, L; Cerri, G; Bello, L
Abstract: Background: It is not clear whether Mood Disorders (MD) and poor Health Related Quality of Life (HRQoL) in glioma patients correlate with clinical and histomolecular features of the tumor or with secondary symptoms associated with treatment. This study assessed the prevalence of MD and decline in HRQoL (with a specific interest in sexuality) in glioma patients, identifying the clinical, imaging and treatment factors associated with these variables. Material and Methods: 260 glioma patients (190 lower grade) were evaluated. Patients were prospectively followed-up from admission to 12 months after surgery, for MD and HRQoL assessment. 115 were asked to fill a questionnaire for sexual life investigation. Clinical, imaging, histomolecular features as well as cognitive functions were evaluated. Variables associated with MD, low HRQoL and sexual life impairment were identified by bivariate analysis. Results: Factors associated with MD and low HRQoL were different in LGGs and HGGs over the course of the disease. In LGGs the effect of adjuvant treatments was prominent in determining the prevalence of MD and poor HRQoL from the third month after surgery onward. In HGGs, MD and poor HRQoL were associated with older age. In both, cognitive deficits were associated with MD. 42% of patients showed dissatisfaction for their sexual life and decrease of sexual intercourses, which were linked to a reduction of libido (22%), astenia (39%), pharmacological therapy (23%), and self-image insecurity(22%). Patients undergoing adjuvant treatments showed a lower sexual satisfaction. Conclusion: Overall the data suggest that worsened quality of life, Incidence of Mood disorder and worsening in sexual life affect a relevant amount of patients affected by glioma. Lack of recovery from functional deficits (language, attentive/executive and motor deficits) and adjuvant therapies (expecially radiotherapy) play a crucial role in determining the emergence of Mood Disorders, low HRQoL and worsened sexual life.